2020
DOI: 10.21203/rs.2.19339/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and antimicrobial susceptibility of Arcobacter species in human stool samples derived from out- and inpatients: the prospective German Arcobacter prevalence study Arcopath

Abstract: Background: Arcobacter species, particularly A. butzleri, but also A. cryaerophilus constitute emerging pathogens causing gastroenteritis in humans. However, isolation of Arcobacter may often fail during routine diagnostic procedures due to the lack of standard protocols. Furthermore, defined breakpoints for the interpretation of antimicrobial susceptibilities of Arcobacter are missing. Hence, reliable epidemiological data of human Arcobacter infections are scarce and lacking for Germany. We therefore performe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 22 publications
(31 reference statements)
3
6
0
Order By: Relevance
“…High resistance rates pose a serious risk to public health as erythromycin is critically important for treatment of campylobacteriosis and it was suggested to be used in Arcobacter infections [68]. As described in previous studies, we also found that the majority of azithromycin MICs (96.2%) were equal to or above the C. jejuni ECOFF (0.25 µg/ml) [19,63]. MIC data for azithromycin indicated the presence of a subpopulation with reduced susceptibility.…”
Section: Antimicrobial Susceptibility Of Isolated Bacteriasupporting
confidence: 76%
See 4 more Smart Citations
“…High resistance rates pose a serious risk to public health as erythromycin is critically important for treatment of campylobacteriosis and it was suggested to be used in Arcobacter infections [68]. As described in previous studies, we also found that the majority of azithromycin MICs (96.2%) were equal to or above the C. jejuni ECOFF (0.25 µg/ml) [19,63]. MIC data for azithromycin indicated the presence of a subpopulation with reduced susceptibility.…”
Section: Antimicrobial Susceptibility Of Isolated Bacteriasupporting
confidence: 76%
“…According to other authors, A. cryaerophilus and A. skirrowii can also be isolated from human stool samples. However, the latter is only rarely detected due to slow growth on culture media and overgrowth by other bacteria, while the prevalence of A. cryaerophilus is up to 6.7-fold lower compared to A. butzleri [14,17,19,36,37]. These are probably the main factors that caused lower species diversity in this study.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations